Practice characteristics and service provision rates of dental hygienists in Australia. Issue 1 (14th August 2017) - Amarasena, N; Teusner, DN; Brennan, DS; Satur, J
Abstract: Introduction: Dental hygienists (DHs) have been practising in Australia since the early 1970s. Objective: This study describes the clinical activity of Australian DHs. Methods: A questionnaire was mailed to members of two professional associations representing DHs. Practitioner characteristics, employment characteristics and clinical activity on a self‐reported typical practice day were collected. The proportion of each service item of all services provided was estimated. Associations between practice characteristics and service provision were assessed by log‐binomial regression models. Results: Adjusted response rate was 60.6%. Of the DHs included in analysis (n=341), 80% were employed in general practice, and nearly all (96%) worked in the private sector. About half (53.7%) of all service provided were preventive services, and one‐fourth (23.9%) were diagnostic. Service provision varied by practice and practitioner characteristics, with the largest variations observed by practice type. Unadjusted analysis showed that general practice DHs provided a higher mean number of periodontal instrumentation and coronal polishing (0.92 vs 0.26), fluoride applications (0.64 vs 0.08), oral examinations (0.51 vs 0.22) and intraoral radiographs (0.33 vs 0.07) per patient visit and a lower mean number of impressions (0.05 vs 0.17) and orthodontic services (0.02 vs 0.59) than specialist practice DHs. In adjusted analysis, rates of periodontal services also significantly varied by practice type; other associations persisted. Conclusion: Service provision of DHs varied by practice type. Practice activity was dominated by provision of preventive services while provision of periodontal treatments, fissure sealants and oral examinations was relatively limited indicating areas in which DHs are possibly underutilized.